Development and characterisation of soluble polymeric particles for pulmonary peptide delivery - Healy, Anne-Marie; Ehrhardt, Carsten; Corrigan, Owen; Tajber, Lidia (My University, 2010)
Pulmonary administration of protein and peptide drugs using inhaled dry powder particles is an interesting alternative to parenteral delivery. The stabilisation of these molecules is essential to the maintenance of biological activity in such inhalation formulations. Here salmon calcitonin (sCT) was co-spray dried with linear or branched PEG (L-PEG and B-PEG) and PVP in order to formulate aerosolisable particles of the bioactive peptide. Co-spray drying L-PEG and PVP resulted in porous particles, with minimal D50 (median volume diameter) and MMAD (mass median aerodynamic diameter) values obtained for a PEG/PVP w/w ratio of 1. For particles based on both L-PEG and B-PEG, an increase in acetone, a poor solvent for the PVP, up to 70 wt% of the spray dried solution led to a decrease in D50 and MMAD. Crystallinity of PEG in the particles ranged between 90-97% when the PVP content varied between 15 and 70 wt%, indicating a low degree of interaction between PVP and PEG. Additionally, dynamic vapour sorption analysis showed that an increase in PVP content increased the particle surface hygroscopicity. Hence, particle properties were adjusted by altering the water/acetone and PEG/PVP ratio in the spray dried solutions. PVP present at the particles surface protects them from melting during the spray drying process but also increases their hygroscopicity, adversely affecting their aerodynamic properties. Targeting a 5 wt% of sCT loading resulted in a loading efficiency of 77.9% and 83.6% with L-PEG and B-PEG based particles, respectively. Loading of sCT in L-PEG or B-PEG based particles modified particle roughness and D50, leading to an increase in MMAD of the L-PEG based particles. However, particles were still considered to be suitable for aerosolisation as their FPFs (fine particle fractions) were higher than 30%. These particles formulated with PVP and PEG allowed sCT biological activity to be maintained when evaluated by measuring cAMP production by T47D cells.
PUBLISHED
Keywords: Pharmacology; Pulmonary inhalation; Immunology, Inflammation & Infection; Nanoscience & Materials; INHALATION; SPRAY DRYING; pharmaceutical polymers